Empathy in television discourse - Imangalikova, Zh.M.; Kusmanova, K.A. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2025)
Pragmatic-oriented research in modern linguistics is increasing. Notably, the use of the term "empathy," which has been applied sporadically in the context of pragmatics, draws attention. It is well known that the term "empathy" belongs to the field of psychology. Currently, its usage in psycholinguistics encompasses the scope of cognitive linguistics. Empathy is frequently observed in the products of television discourse and has become a subject of research in this area. From this perspective, it is possible to highlight the need for and relevance of the development of psycholinguistics and fundamental cognitive studies. The content of the article examines the manifestation of empathy in television discourse and its application in relation to the cognitive natural essence of language. The study aims to draw attention to the peculiar emotional states of individuals and the expression of the "language of feelings" in such moments. To achieve effective objectives, the study sets tasks to analyze empathy in television news and the emotional state of recipients during their perception and feeling of television programs, using linguistic (verbal) and non-linguistic (non-verbal) elements. The research results can be included in theoretical studies that integrate cognitive linguistics and psychology. The findings may have a methodological impact on applied linguistics and psychological studies.